Modul Teknik Self-Instruction untuk Penerapan Nilai Waja Sampai Kaputing (Wasaka) - Nina Permata Sari; Sulistiyana Sulistiyana; M. Arli Rusandi (Bulletin of Counseling and Psychotherapy, 2022)
This study aims to determine the procedure for developing the self-study technique module and the effectiveness of the self-instruction technique module in applying the Waja Sampai Kaputing (wasaka) values. Wasaka means it is a well-known motto from the province of South Kalimantan, which means that endeavor until the end. This type of research is research and development with the ADDIE model, namely Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques in the form of observation and questionnaires. The module was tested on 21 students. Data analysis used paired sample T-test. The result of this research is the creation of a self-instruction technique module. It has a significant effect on the application of wasaka values to FKIP Universitas Lambung Mangkurat students with indicators of hard work, toughness, responsibility, and independence, so that the self-instruction technique module is effective in applying the values of Waja Sampai Kaputing (wasaka) on students.